Perlindungan Hukum terhadap Korban Human Trafficking dalam Perspektif Hak Asasi Manusia - agus takariawan; sherly ayuna putri (Jurnal Hukum IUS QUIA IUSTUM, 2018)
This study discussed the forms of legal protection for trafficking victims in the perspective of human rights and the mechanism of providing restitution and legal protection for trafficking victims in the perspective of human rights. The study used normative legal method with statute and case approahes. The data analysis was descriptive qualitative. The results concludes that the legal protection for trafficking victims are in the forms of restitution, compensation, and rehabilitation, while some other forms of legal protection are not applicable due to various factors. One of the inhibiting factors is the absence of a clear mechanism for paying restitution to trafficking victims. Thus, Article 48 in Law No.21 of 2007 concerning Human Trafficking is not applicable so that either the article needs amendment or its implementing regulation is made, so that the rights of victims in the trial can be implemented